EDUCATION SERVICE MARKETING STRATEGY IN INCREASING THE NUMBER OF STUDENTS IN THE VOCATIONAL SCHOOL OF EDUCATION VOCATIONAL SCHOOL OF BP (PESANTREN BASED) SUBULUL HUDA KEBONSARI, MADIUN - Mella Mardayanti; Bambang Mursito; Sudarwati (Sekolah Tinggi Agama Islam Nahdlatul Ulama Madiun, 2021)
Abstract: This study aims to increase the number of students at SMK BP (Pesantren-based) Subulul Huda Kebonsari, Madiun City, and the existence of competition between educational institutions. So this research was carried out aimed at (1) Knowing the marketing strategy of educational services at SMK BP (Based on Islamic Boarding Schools) Subulul Huda Kebonsari, Madiun City (2) Knowing the supporting and inhibiting factors in the marketing strategy of educational services at SMK BP (Pesantren-based) Subulul Huda Kebonsari Kota Madiun (3) Knowing the implementation of the education service marketing strategy at SMK BP (Pesantren-based) Subulul Huda Kebonsari, Madiun City (4) Knowing the extent of the success achieved. This research uses a descriptive qualitative approach. This research was conducted at SMK BP (Pesantren based) Subulul Huda Kebonsari, Madiun City. The subject of this research is the Principal of the School. The informants of this study were the Head of Administration, Public Relations, Student Affairs, and Students. Data collection techniques using observation, interviews, and documentation and checking the validity of the data used triangulation of sources and methods. The data analysis technique uses an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. The results showed that: (1) The marketing strategy of educational services carried out by SMK BP (Pesantren-based) Subulul Huda Kebonsari, Madiun City is: (a) Direct marketing, namely by utilizing IT, print, and electronic media. (b) Indirect marketing, namely by conducting outreach to SMP / MTS and the community. (2) Supporting factors, among others, teachers teach according to their fields, geographic location, low prices, high trust from the community. While the inhibiting factors include the number of competitors between institutions, and there are still students who are forced to go to school because of parents (3) The results achieved can compete in terms of products, processes, human resources and have the characteristics of Islamic Boarding School-Based Vocational Schools in both extracurricular and intracurricular fields.